Proteksi Katodik Menggunakan Zinc Anode Untuk Menghambat Korosi Pada Lambung Kapal Port Link Vii Jakarta - Teddy Ihza Mahendra; Dwisetiono Dwisetiono (Departemen Teknik Kelautan Universitas Hasanuddin, 2022)
Cathodic protection is a thermodynamic corrosion rate control method by treating metal structures as cathodes. Cathodic protection is very important to reduce the corrosion rate of the underwater surface area of ​​the hull plate. This protection is affixed to parts of the ship that are susceptible to seawater corrosion, more precisely located below the water line. Most of the damage to the ship's steel construction plate is caused by the corrosion process. As a result of this corrosion causes substantial material losses, so protection is needed to prevent corrosion by using cathodic methods. Basically, corrosion control methods can be grouped into two groups, namely kinetic methods and thermodynamic methods. In the kinetic method of controlling corrosion, it is done by providing barriers to the interaction with the environment so that the corrosion rate can be reduced, but the tendency for corrosion to occur itself is not resolved, so that if the obstacles are removed corrosion will take place again soon. The application of cathodic protection is often combined with coatings. Its purpose is to protect the steel when the coating is damaged